2015
DOI: 10.1073/pnas.1523762113
|View full text |Cite
|
Sign up to set email alerts
|

Functions of vasopressin and oxytocin in bone mass regulation

Abstract: Prior studies show that oxytocin (Oxt) and vasopressin (Avp) have opposing actions on the skeleton exerted through high-affinity G protein-coupled receptors. We explored whether Avp and Oxtr can share their receptors in the regulation of bone formation by osteoblasts. We show that the Avp receptor 1α (Avpr1α) and the Oxt receptor (Oxtr) have opposing effects on bone mass: Oxtr −/− mice have osteopenia, and Avpr1α −/− mice display a high bone mass phenotype. More notably, this high bone mass phenotype is revers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 35 publications
3
49
0
Order By: Relevance
“…This high bone mass phenotype was also observed in AVPR1A-deficient mice [111]. In contrast, AVPR2 does not have a significant role in bone remodeling, since the specific AVPR2 inhibitor tolvaptan does not affect bone formation or bone mass [112]. Collectively, the data establish a primary role for AVP signaling in bone mass regulation.…”
Section: Vasopressinsupporting
confidence: 53%
See 2 more Smart Citations
“…This high bone mass phenotype was also observed in AVPR1A-deficient mice [111]. In contrast, AVPR2 does not have a significant role in bone remodeling, since the specific AVPR2 inhibitor tolvaptan does not affect bone formation or bone mass [112]. Collectively, the data establish a primary role for AVP signaling in bone mass regulation.…”
Section: Vasopressinsupporting
confidence: 53%
“…AVPR1A and OXTR have opposing effects on bone mass. Notably, the deletion of OXTR in OXTR -/-:AVPR1A -/-double-mutant mice reversed the high bone mass phenotype in AVPR1A -/-mice [112]. While OXTR deletion in AVPR1A -/-cells inhibits AVP-stimulated gene expression, OXTR is dispensable for the anti-osteoblastic action of AVP [112].…”
Section: Vasopressinmentioning
confidence: 95%
See 1 more Smart Citation
“…Hyponatraemia is associated with reduced BMD in a rodent model of SIAD 130 , and oxytocin deficiency is also associated with low BMD in oxytocin and oxytocin receptor null mice 131 . Similar to preclinical studies, hyponatraemia 129 is associated with decreased BMD in women with anorexia nervosa independent of BMI; low nocturnal serum oxytocin levels 84 are also associated with decreased BMD.…”
Section: Skeletal Integritymentioning
confidence: 95%
“…Interestingly, many of the published beneficial health effects of oxytocin overlap with recognized L. reuteri health-promoting attributes. Indeed, as with L. reuteri (Britton et al, 2014; Collins et al, 2016; Poutahidis et al, 2013a,b; Varian et al, 2016a,b, 2014; Zhang et al, 2015b), the exogenous administration of oxytocin has been shown to accelerate wound healing (Gavrilenko et al, 2003; Gouin et al, 2010; Vitalo et al, 2009), counteract obesity (Barengolts, 2016; Blevins and Baskin, 2015), suppress uncontrolled inflammation (Wang et al, 2015) and prevent muscle wasting (Costa et al, 2014; Elabd et al, 2014) and bone loss (Colaianni et al, 2014; Sun et al, 2016; Tamma et al, 2009). …”
Section: Introductionmentioning
confidence: 99%